2016
DOI: 10.1016/j.bjorl.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Facial trauma among victims of terrestrial transport accidents

Abstract: The occurrence of facial trauma in terrestrial transport accident victims tends to affect a greater proportion of young and male subjects, and the most prevalent accidents involve motorcycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 31 publications
7
22
0
2
Order By: Relevance
“…In this case, corroborating with the study of Miranda and Sarti [29], which brings in total 51.4% of cases between the ages mentioned above, as well as other studies [30][31][32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this case, corroborating with the study of Miranda and Sarti [29], which brings in total 51.4% of cases between the ages mentioned above, as well as other studies [30][31][32].…”
Section: Discussionsupporting
confidence: 92%
“…Because it is a public hospital in facial and brain trauma care, the number of patients with it is bigger, however, in the literature is found that most of the accidents resulted in traumas of upper and lower limbs [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…negative consequences for victims in the physical, emotional and functional aspects, 27 and are considered a serious public health problem in developed and developing countries. 28 In most road traffic accidents, the presence of bone fractures was verified, including bones of the skull and maxilla, corroborating findings obtained in India. 29 These injuries may be related to osteoporosis, common in the elderly, since this disease is a risk factor for fractures.…”
Section: Discussionsupporting
confidence: 81%
“…This is further enhanced by the number of skull x-rays performed on a daily basis, as the population has increased access to dental care, to diagnose, plan and/or check different clinical treatments (5,15).…”
Section: Discussionmentioning
confidence: 99%